Egypt's Policy Pathways - International Water Management Institute (International Water Management Institute, 2024)
Join us in Egypt for the final stop on the Policy Pathways world tour! This week, we delve into the food, land, and water challenges confronting Egypt as the country grapples with the necessity for enhanced resource quality amidst rapid population growth.